2015
DOI: 10.1155/2015/323128
|View full text |Cite
|
Sign up to set email alerts
|

Germination Ecology of Arundinaria alpina (K. Schum.) and Oxytenanthera abyssinica (A. Rich.) Munro Seeds: Indigenous Bamboo Species in Ethiopia

Abstract: Highland bamboo (Arundinaria alpina) and lowland bamboo (Oxytenanthera abyssinica) are indigenous to Ethiopia and endemic to Africa. Seeds of A. alpina were collected from Dawa Wereda (District), while O. abyssinica seeds were collected from Pawe and Sherkole Weredas. In this study, seed presowing treatments, effects of dry heat, moist heat, and light/dark treatments on the germination of seeds were tested. The averages were of 59,416 and 8,393 seeds contained within 1 kg of A. alpina and O. abyssinica seeds w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 7 publications
0
13
1
Order By: Relevance
“…The seed germination period of Oldeania alpine was reported to be 8 days, with the germination starting on the 4th day after sowing (Zhang et al, 2016 ). Seed germination was reported to start on the 7th and completed on the 17th day in Arundinaria alpina , and started on the 4th day and completed on the 9th day in Oxytenanthera abyssinica (Bahru et al, 2015 ). Seeds of D. brandisii achieved their highest germination rates on the 4th day and finished their germination in 21 days.…”
Section: Discussionmentioning
confidence: 99%
“…The seed germination period of Oldeania alpine was reported to be 8 days, with the germination starting on the 4th day after sowing (Zhang et al, 2016 ). Seed germination was reported to start on the 7th and completed on the 17th day in Arundinaria alpina , and started on the 4th day and completed on the 9th day in Oxytenanthera abyssinica (Bahru et al, 2015 ). Seeds of D. brandisii achieved their highest germination rates on the 4th day and finished their germination in 21 days.…”
Section: Discussionmentioning
confidence: 99%
“…A slightly higher survival rate of O. abyssinica seedlings at Pawe provenance (91%) than Sherkole provenance (90%) revealed that the seed sources further contributed to the successful survival rate of seedlings at green house. Former research conducted by [11] assured that Pawe provenance has better seed germination and seed weight than Sherkole provenance. Nevertheless, both provenances further have higher potential in producing viable and vigour seeds [12].…”
Section: Discussionmentioning
confidence: 99%
“…Raising at Laboratory. Untreated O. abyssinica seeds, which have best germination percentage, were sowed at laboratory [11] on Petri-dishes. The filter paper was kept moist with distilled water as much as possible throughout the entire experimental period.…”
Section: Seedlingmentioning
confidence: 99%
See 2 more Smart Citations